Does Neutral Affect Exist? How Challenging Three Beliefs About Neutral Affect Can Advance Affective Research - Gasper, Karen; Spencer, Lauren A.; Hu, Danfei (Frontiers in Psychology, 2019)
Researchers interested in affect have often questioned the existence of neutral affective states. In this paper, we review and challenge three beliefs that researchers might hold about neutral affect. These beliefs are: (1) it is not possible to feel neutral because people are always feeling something, (2) neutrality is not an affective state because affect must be positively or negatively valenced, and (3) neutral affect is unimportant because it does not influence cognition or behavior. We review the reasons these beliefs might exist and provide empirical evidence that questions them. Specifically, we argue that neutral affect is a felt experience that provides important valence-relevant information, which influences cognition and behavior. By dispelling these beliefs about neutral affect, we hope to shine a light on the assumptions that researchers hold about the nature of affect and to provide novel theoretical and methodological perspectives that help advance our understanding of the affective landscape.